Design and analysis of electrical energy storage demonstration projects on UK distribution networks. (1st January 2015) - Lyons, P.F.; Wade, N.S.; Jiang, T.; Taylor, P.C.; Hashiesh, F.; Michel, M.; Miller, D.
Highlights: Results of an EES system demonstration project carried out in the UK. Approaches to the design of trials for EES and observation on their application. A formalised methodology for analysis of smart grids trials. Validated models of energy storage. Capability of EES to connect larger quantities of heat pumps and PV is evaluated. Abstract: The UK government's CO2 emissions targets will require electrification of much of the country's infrastructure with low carbon technologies such as photovoltaic panels, electric vehicles and heat pumps. The large scale proliferation of these technologies will necessitate major changes to the planning and operation of distribution networks. Distribution network operators are trialling electrical energy storage (EES) across their networks to increase their understanding of the contribution that it can make to enable the expected paradigm shift in generation and consumption of electricity. In order to evaluate a range of applications for EES, including voltage control and power flow management, installations have taken place at various distribution network locations and voltage levels. This article reports on trial design approaches and their application to a UK trial of an EES system to ensure broad applicability of the results. Results from these trials of an EES system, low carbon technologies and trial distribution networks are used to develop validated power system models. These models are used to evaluate, using a formalised methodology, the impact that EES could have on the design and operation of future distribution networks.